Formulation of ibuprofen-modified release hydrophilic and lipid matrix tablets using co-processed excipients - Lazić, Irina; Kučević, Sabina; Ćirin-Varadjan, Slobodanka; Aleksić, Ivana; Djuriš, Jelena (Archives of Pharmacy, 2022)
Formulation of modified-release ibuprofen tablets presents a challenge due to its high dose, limited compressibility and compactibility. The potential for preparing ibuprofen modified release matrix tablets, by direct compression procedure using co-processed excipients, was evaluated. Co-processed excipients of hydrophilic and lipid properties were used. Commercially available co-processed excipient based on hydroxypropylmethylcellulose and lactose (RetaLac®), as well as co-processed excipient made in-house, using lipid matrix forming agent based on glyceryl palmitostearate (Precirol®) and lactose were used. The influence of co-processed excipient type, ibuprofen ammount in tablets (25% and 50%) and the compression load (100 and 500 kg) on the mechanical properties of the hydrophilic or lipid matrix tablets was evaluated. Also, ibuprofen release rate was investigated in a rotating paddle apparatus with medium change (0.1M HCl and phosphate buffer pH 6.8). The tensile strength of formulations was in the range of 0.5-2 MPa. The compression load and the co-processed excipient type showed a significant effect on tensile strength. Ibuprofen was released in a sustained manner from all formulations, with the amount released after 8 hours varying from 35 to 80%, depending on the matrix forming material type. The release of ibuprofen from lipid matrix tablets was slower compared to hydrophilic tablets, with neither the compression load nor the ibuprofen content showing a significant effect. Zero-order kinetics was achieved from both types of matrix tablets. Based on the obtained results, it can be concluded that co-processed excipients enable direct compression of ibuprofen modified release hydrophilic and lipid matrix tablets.